The Conceptualization and Operationalization of Cultural Tolerance: Adopting Positive Psychology Perspective - Linoa, Mitshel; H.M. Hashim, Intan; Ricardoc, Ricky (School of Social Sciences, USM, 2017)
Tolerance is a concept commonly found in field of study such as sociology, political sociology, multiculturalism and liberalism, but not in positive psychology. This concept paper aims to conceptualize and operationalize cultural tolerance by adopting positive psychology perspective. It begins with reviewing past literatures on tolerance from various perspective and comparing the definitions, complexities, challenges and gaps. Through addressing the conceptual gaps of tolerance from various perspectives and taking into consideration the positive psychology philosophy and theories, a distinctive concept and operational definition of cultural tolerance from positive psychology are presented.